Chemoprotection and Immunostimulation of Alpha-Lipoic Acid Against Chlorpyrifos-Induced Toxicosis in Nile Tilapia, Oreochromis niloticus - Bilal A. Paray; Eijaz A. Bhat; Abdulkadir O. Adebayo; Femi J. Fawole; Ibrahim Adeshina (Scientifica)
This paper examined the chemoprotective and immunomodulatory effects of alpha-lipoic acid (ALA) against chlorpyrifos (CPL)-induced toxicosis in Nile tilapia, Oreochromis niloticus. Fish (n = 120, mean weight = 8.8 ± 0.6 g) were divided into 12 tanks (100-L capacity, 10 fish/tank) to represent two groups. Group 1 (60 fish) was fed a diet (300 g/kg crude protein) containing 40 mg ALA/kg feed, while Group 2 (60 fish) was fed a basal diet without ALA. Then, 30 fish from each group were exposed to 450 μg CPL/L. Thus, the experimental treatments were control, CPL (basal diet and exposed to CPL), ALA (ALA-based diet), and ALA + CPL (ALA-based and exposed to CPL) for 14 days. Fish fed with ALA alone showed significantly (p=0.001) higher survival rates (100%), improved hematological and biochemical profiles, enhanced antioxidant activity, and stronger immune responses than CPL-exposed fish alone. CPL exposure caused severe physiological disorders and histological damage, particularly in the liver. However, ALA + CPL interactions mitigated these adverse effects, restoring tissue integrity and functionality. The findings underscore ALA’s potential as a dietary intervention to reduce environmental toxicant-induced stress in aquaculture, improving fish health and resilience against toxins.